Evidence for expression of promoterless GFP cassette: Is GFP an ideal reporter gene in biotechnology science? - Zahra Mohammadi (Research in Pharmaceutical Sciences, 2019)
Green fluorescent protein (GFP) has played an important role in biochemistry and cell biology as a reporter gene. It has been used to assess the potency of promoters for recombinant protein production. This investigation reveals evidences suggesting that the gfp GFP gene (EGFP) could be expressed without the promoter. In a study, a pLenti-F/GFP vector was constructed with the purpose to allow GFP expression in transduced cells but not in packaging cells; however, after transfecting the HEK293T cell line, GFP gene was expressed, compared to pLOX/CWgfp-transfected cells showed expression lag, lower levels and reduced percentage of GFP expression in the cells. This unexpected result could be due to auto transduction in packaging cell, possible retrotransposon activity in the cell line, possible contamination of pLenti-F/GFP with the pLOX/CWgfp and possible presence of a promoter within backbone of the vector. All the possibilities were ruled out. To exclude the possibility that a sequence within the region might act as a promoter, the fragment to be transfected was minimized to a region containing “from the start of the GFP gene to 5’LTR R”. The GFP gene was again expressed. Therefore, our findings suggest the EGFP does not need promoter for expression. This should appeal to the researchers designing GFP based assays to evaluate the potency of promoters, since possible aberrant expression may have a potential to influence on the results of a planned experiment.